Mitochondrial phylogeography of the European pond turtle, Emys orbicularis (Linnaeus 1758) - Lenk, Peter; Wink, Michael (Molecular ecology, 1999)
The phylogeny and phylogeography of Emys orbicularis was inferred from mitochondrial nucleotide sequences of the cytochrome b gene analysed by DNA sequencing and RNA heteroduplex analysis. Within the family Emydidae the monotypic genus Emys is affiliated with the nearctic taxa Emydoidea blandingii and Clemmys marmorata. The analysis of 423 individuals of E. orbicularis, originating throughout its distribution range, revealed a remarkable intraspecific differentiation in 20 different haplotypes with distinct geographical ranges. Maximum parsimony analysis produced a star-like phylogeny with seven main lineages which may reflect separations in the late Pliocene. The haplotype distribution examined by partial Mantel tests and analysis of molecular variance revealed a substantial effect of glacial periods. This historical perspective suggests the existence of multiple glacial refugia and considerable Holocene range expansion which was modulated by climatic traits. Further support is gained for the occurrence of long-term parapatry in glacial refugia.